2008
DOI: 10.1093/mutage/gen004
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to mineral fibres. Biomarkers of oxidative damage and antioxidant defence and associations with DNA damage and repair

Abstract: In order to study the effect of mineral wool exposure on oxidative DNA damage and lipid peroxidation, an epidemiological study was conducted in a mineral wool factory in Slovakia. Altogether 141 subjects were investigated (21-58 years old), 43 controls (20 men and 23 women: 27 non-smokers, 16 smokers) and 98 exposed (75 men and 23 women: 61 non-smokers, 37 smokers). We found higher malondialdehyde (MDA) levels in the group of all exposed workers (P = 0.025) and in exposed non-smokers (P = 0.003) and a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 47 publications
3
9
0
1
Order By: Relevance
“…[2325272847] There are evidences that certain vegetables and fruits contain anticlastogenic agents and have antioxidant properties. [4849] Non-significant increase in non-vegetarian workers was observed and was in agreement with the results of Giovannelli et al [50] and Dhawan et al . [51] No significant relationship has been detected between DNA damage and smoking.…”
Section: Discussionsupporting
confidence: 91%
“…[2325272847] There are evidences that certain vegetables and fruits contain anticlastogenic agents and have antioxidant properties. [4849] Non-significant increase in non-vegetarian workers was observed and was in agreement with the results of Giovannelli et al [50] and Dhawan et al . [51] No significant relationship has been detected between DNA damage and smoking.…”
Section: Discussionsupporting
confidence: 91%
“…Inal et al (2001) also observed significantly higher MDA levels in healthy individuals with respect to age. Staruchova et al (2008) found an increase in MDA levels in workers of a mineral wool factory in Slovakia, and similar results were obtained in a group of radiology unit employees and in operating room personnel (Malekirad et al 2005a, b).…”
Section: Discussionsupporting
confidence: 71%
“…In addition to biomarkers of immunotoxicity, biomarkers of genotoxicity (Beňo et al, 2005;Dusinska et al, 2004;Horská et al, 2006;Topinka et al, 2004;, oxidative damage and antioxidant defense (Staruchova et al, 2008) were also examined in the same cohorts. The studies involved workers with at least 5 years' exposure to asbestos, rock wool and glass fibers, respectively, at 3 industrial plants in Slovakia.…”
Section: Molecular Epidemiological Studies In Human Populationmentioning
confidence: 99%